Spectral analysis of aerosol optical depth over aeronet sites of Nepal - Acharya, Aashma; Adhikari, Binod; Bhattarai, Pratik; Jha, Gopal; Acharya, Shambhu; Shah, Ritesh (BIBECHANA, 2020)
The suspended particle aerosols especially anthropogenic are recognized to have degradation in the quality of the atmosphere and one of the factors to cause uncertainty in climate. In this paper, we have investigated the trend of the parameter ‘Aerosol Optical depth’ and by application of spectral based wavelet analysis; we extracted spatial and temporal variation over the selected AERONET sites of Nepal. We have taken the site Kyanjin_gompa, Lumbini, Pokhara and Kathmandu under the consideration of our study because of their geographical variability which is a significant factor for causing variation in local as well as global circulation of aerosols. As per data retrieved from Ground-Based remote sensing system for the year 2018 over the site Kyanjin gompa, Lumbini and Pokhara and for the year 2016 over the Kathmandu, we extracted the periodicity and frequency of the variation in AOD for each site by the application of continuous wavelet analysis on AOD at three different wavelengths. On reviewing the previous studies, it is seen that the area lying at the Indo-Gangetic plain exhibit high aerosol loading in comparison with the Himalayan foothills and central Himalayas of Nepal. We found not only the higher aerosol loading in atmosphere over site Lumbini but also higher periodicity. Likewise, we also found Pokhara as highly polluted as Lumbini. The investigation of data records over the site Kathmandu has shown increment in aerosol loading in the year 2016 compared with previous years. BIBECHANA 17 (2020) 80-88